Evaluation of the Safety Conditions of Shiraz University of Medical Sciences Educational Hospitals Using Safety Audit Technique - Mohammad Amin Norozi; Mahdi Jahangiri; Forough Zare Derisi (Tehran University of Medical Sciences, 2012)
Background and Aim: Hospitals are among the most important establishments providing health services, in which -- due to special hazards -- the observance of safety principles is of great importance. This research aimed to study the safety conditions at educational hospitals of Shiraz University of Medical Sciences(SUMS).Materials and Methods: This cross-sectional descriptive study was conducted in all educational hospitals in Shiraz and their safety status was investigated using safety audit technique. To this end, audit checklists were prepared and completed through observation, interview with managers and officials of various departments as well as studying the related documents. Then, based on the realization of safety requirements, hospitals were classified into three levels of poor (lower than 50%), medium (5o-75%), and good (higher than75%).Results: The mean realization of safety requirements in the studied hospitals was 58 percent. The highest and lowest levels of realization of safety requirements were related to radiation safety and safety management, respectively. Safety status was evaluated as poor in 25% and medium in 75% of the studied hospitals.Conclusion: The safety conditions of the studied hospitals, especially as regards safety management, emergency response plan, and fire safety aspects were relatively poor. The most important reason for that was the lack of clarity of responsibilities and of safety organizational structure. To improve the safety status, hospitals are required to establish the Occupational Health and Safety Management System (OHSAS 18001).